Broadening sarbecovirus neutralization with bispecific antibodies combining distinct conserved targets on the receptor binding domain - Denise Guerra; Laura Radić; Mitch Brinkkemper; Meliawati Poniman; Lara van der Maas; Jonathan L. Torres; Andrew B. Ward; Kwinten Sliepen; Janke Schinkel; Rogier W. Sanders; Marit J. van Gils; Tim Beaumont (Human Vaccines & Immunotherapeutics)
Monoclonal neutralizing antibodies (mAbs) are considered an important prophylactic against SARS-CoV-2 infection in at-risk populations and a strategy to counteract future sarbecovirus-induced disease. However, most mAbs isolated so far neutralize only a few sarbecovirus strains. Therefore, there is a growing interest in bispecific antibodies (bsAbs) which can simultaneously target different spike epitopes and thereby increase neutralizing breadth and prevent viral escape. Here, we generate and characterize a panel of 30 novel broadly reactive bsAbs using an efficient controlled Fab-arm exchange protocol. We specifically combine some of the broadest mAbs described so far, which target conserved epitopes on the receptor binding domain (RBD). Several bsAbs show superior cross-binding and neutralization compared to the parental mAbs and cocktails against sarbecoviruses from diverse clades, including recent SARS-CoV-2 variants. BsAbs which include mAb COVA2–02 are among the most potent and broad combinations. As a result, we study the unknown epitope of COVA2–02 and show that this mAb targets a distinct conserved region at the base of the RBD, which could be of interest when designing next-generation bsAb constructs to contribute to a better pandemic preparedness.